PENGARUH INHALASI LEMON TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER PERTAMA - Herty, Azuri Judia; Setiowati, Oktasha Tri; Asiah, Asiah; Haryanti, Syarifah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Nausea and vomiting during pregnancy is generally referred to as morning sickness, is experienced by about 70% to 80% of pregnant women and is a phenomenon that often occurs between five and 12 weeks of gestation. During pregnancy there are various kinds of problems or complications that often occur, such as feelings of nausea and vomiting that are very often experienced by pregnant women which is one of the first symptoms during pregnancy. Situations and conditions like this can slow the circulation of blood and can result in a lack of oxygen and food supply to the tissues so that it can endanger the health of the mother and the fetus.Efforts to treat hyperemesis gravidarum are grouped into 2 namely pharmacological and non-pharmacological therapies. One of the non-pharmacological therapies used is aromatherapy with lemon-based ingredients. Lemon is one of the fruits that is considered a drug that is quite safe when used in pregnancy. The administration of lemon aromatherapy inhalation is efficient and effective in reducing the frequency of nausea and vomiting for pregnant women. Inhalation of lemon aromatherapy is a part that can be determined as a complementary therapy to reduce the frequency of nausea and vomiting in the care of pregnant women.Lemon can reduce complaints in hyperemesis gravidarum, the aroma produced will stimulate the work of brain neurochemical cells and can stabilize the nervous system.